2018
DOI: 10.1148/radiol.2017161548
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Tumor Shrinkage during Neoadjuvant Chemotherapy Is Associated with Prognosis in Low-Grade Luminal Early Breast Cancer

Abstract: Purpose To evaluate the association between tumor shrinkage patterns shown with magnetic resonance (MR) imaging during neoadjuvant chemotherapy (NAC) and prognosis in patients with low-grade luminal breast cancer. Materials and Methods This retrospective study was approved by the institutional review board and informed consent was obtained from all subjects. The low-grade luminal breast cancer was defined as hormone receptor-positive and human epidermal growth factor receptor 2-negative with nuclear grades 1 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 29 publications
0
52
3
Order By: Relevance
“…Limitations of the present study could be the low number of cases and the exclusion of patients receiving primary hormone therapy (PHT). Fukada and coworkers have reported that CS is significantly more frequent in luminal breast cancers following PHT, and these patients had significantly better outcome than patients having other patterns [42]. In contrast, there was no significant correlation between regression patterns and molecular subtypes in present work.…”
Section: Discussioncontrasting
confidence: 74%
“…Limitations of the present study could be the low number of cases and the exclusion of patients receiving primary hormone therapy (PHT). Fukada and coworkers have reported that CS is significantly more frequent in luminal breast cancers following PHT, and these patients had significantly better outcome than patients having other patterns [42]. In contrast, there was no significant correlation between regression patterns and molecular subtypes in present work.…”
Section: Discussioncontrasting
confidence: 74%
“…Ninety‐nine percent of respondents performed post‐NACT imaging: MRI‐76%, ultrasound‐41%, and mammography‐29%. Studies have shown that MRI can be useful in predicting pathological response and can be used to differentiate between therapy‐induced nonvasularised fibrosis and residual tumors . One study showed that end‐of‐NACT lesion size measured on MRI did not differ from the histological size with a sensitivity of 87% and accuracy 77%.…”
mentioning
confidence: 99%
“…Limitations of the present study could be the low number of cases and the exclusion of patients receiving PHT. Fukada and coworkers have reported that CS is significantly more frequent in luminal breast cancers following PHT, and these patients had significantly better outcome than patients having other patterns [127]. In contrast, there was no significant correlation between regression patterns and molecular subtypes in the present work.…”
Section: Evaluation Of Regression Heterogeneity Incontrasting
confidence: 80%